The alleviative effects of green synthesized copper oxide nanoparticles against oxidative stress, hepato-renal alterations, and immune suppression induced by Staphylococcus aureus infection in Clarias gariepinus - Afaf N. Abdel Rahman; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Nasreddin R. Rhouma; Haidy T. Zaki; Samah S. Khalil; Mahmoud M. El-Saber; Simon J. Davies; Abdelhakeem El-Murr; Rowida E. Ibrahim (Aquaculture Reports, 2023)
Copper oxide nanoparticles (CuONPs) have attracted much interest due to their catalytic and anti-bacterial activity. The present study exhibits that Moringa oleifera synthesized CuONPs (MS-CuONPs) might provide a promising anti-bacterial substitute for conventional antibiotics to treat Staphylococcus aureus infection in African catfish. MS-CuONPs showed an in vitro anti-bacterial activity (21.33 ± 0.80 mm inhibition zone) against S. aureus. One hundred-twenty fish (average weight: 120 ± 5.36 g) were haphazardly allocated into four groups in triplicates for 10 days (control, MS-CuONPs, S. aureus, and MS-CuONPs + S. aureus), where a concentration of 0.1 mg/L of MS-CuONPs was used. The S. aureus infection induced a marked reduction in immunological (lysozyme, complement 3, and nitric oxide), protein profile (total protein, total globulins, and albumin), and hepatic antioxidant (total antioxidant capacity, superoxide dismutase, and glutathione peroxidase) indices as well as a higher mortality rate (46.67%). Moreover, an apparent elevation in the values of tumor necrosis factor-alpha (TNF-α), hepatic malondialdehyde (MDA), stress biomarkers (cortisol and glucose), and hepato-renal indicators (aspartate aminotransferase, alkaline phosphatase, alanine aminotransferase, creatinine, and urea) were the consequences of S. aureus infection. Interestingly, treatment of S. aureus-infected fish with MS-CuONPs improved these parameters. According to these outcomes, MS-CuONPs as a water additive can protect fish against the negative impacts of S. aureus and can be used a promise anti-bacterial agent.